COMPARATIVE STUDY OF DRYING METHODS FOR PREPARATION OF TURMERIC POWDER - Charoenchai, Laksana; Monton, Chaowalit; Luprasong, Chitradee; Kraisintu, Krisana (Interprofessional Journal of Health Sciences, 2019)
Turmeric powder is produced from Curcuma longa rhizomes and is used in medicinal products and cosmetics. One important step of the preparation of turmeric powder is the drying method. The objective of this study was to compare drying methods used in cultivating area to decrease processing time while maintaining the quality of turmeric powder. Drying methods were drying (1) under sunlight, (2) in gas hot air oven, (3) in electric hot air oven and (4) hot air oven combined with microwave oven. Curcuma longa rhizomes harvested at 18 months were collected from Banthakhun Suratthani province, Thailand. Total curcuminoid content was analyzed using spectrophotometric method as defined in Thai Herbal Pharmacopoeia (THP). Volatile oil content was determined using distillation method. Total curcuminoid content was in the range 6.76-8.67 %w/w, which was higher than 5.0 %w/w specified by THP. Using the method of hot air oven at 60 °C for 40-90 minutes combined with microwave oven for 30-40 minutes was the shortest drying time of the four methods. There was no statistical difference of total curcuminoid amount among these drying methods by ANOVA. In addition, volatile oil content of all samples was in the range of 7.99-8.99 %v/w, which was above 6.0% v/w of standard criteria of THP.